Phytochemical screening and antimicrobial assay of some Nepalese medicinal plants - Maharjan, Bijaya Laxmi; Mainali, Smritri; Baral, Bikash (Scientific World, 2011)
Medicinal plants constitute several bioactive compounds that are antimicrobial. Due to the extensive need of the new antimicrobial compounds of plant origin the study was conducted. The present paper deals with the qualitative phytochemical analysis and antimicrobial assay of methanolic extracts of four medicinal plants namely Butea monosperma (seed), Cissampelos pareira (root), Myrica esculenta (bark) and Selinum tenuifolium (root). The standard phytochemical test of the extracts revealed the presence of polyphenols, glycosides and coumarins in all the plant extracts. For the in-vitro antimicrobial assay, agar well diffusion method was employed against human pathogenic bacteria (11) and phytopathogenic fungi (5). The extracts of C. pareira, M. esculenta were effective against all the tested bacteria and fungi which indicated their broad spectrum antimicrobial potential. The extract of B. monosperma was effective against B. subtilis, S. typhi, Acinetobacter species, F. oxysporum, F. moniliformie, E. turticum and S. roulfsii. But the extract of S. tenuifolium was ineffective against all the tested bacteria but was effective against all the fungal strains revealing it to have more antifungal potential. The antimicrobial properties of these plant extracts may be due to the presence of various secondary metabolites. The results provided evidence that the studied plants might indeed be employed in the management of microbial infections. Key words: Plant extract; Phytochemicals; Antibacterial; Antifungal DOI: http://dx.doi.org/10.3126/sw.v9i9.5526 SW 2011; 9(9): 90-92